Antecedents of the adoption of Social Media Marketing by micro and small enterprises - Gouveia, Renata Edvania Costa; Aguiar, Edvan Cruz (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The adoption of Social Media Marketing (SMM) is increasingly present in the daily life of companies. However, little is known about this phenomenon in the context of micro and small businesses (MSEs). The research aimed to analyze the SMM adoption process by MSEs, based on a study with 338 entrepreneurs linked to the Brazilian Micro and Small Business Support System (Sebrae), using Structural Equation Modeling. It was found that technical knowledge, cost reduction, and pressure from customers and competitors generate benefits perceived by entrepreneurs concerning the use of the tool, leading to a higher level of use. The work contributes to the step in which it brings evidence that helps to understand the determinants of adopting SMM in the context of MSEs.